La dimensión laboral de la responsabilidad social empresarial (2011)
The ethics of care, which is based on the notion of Corporate Social Responsibility, CSR, labor issues in one of its main pillars. However, it still misses more attention from companies in regard to the way how they could strengthen the labor dimensions of their CSR policies. In tandem with labor issues monopolize the spaces of free trade, it is necessary to develop higher levels of consciousness in the companies on this delicate subject, as from the bowels of global stakeholders. So important are these issues, which might well be on the verge of what I would call Corporate Social Responsibility Labor as a component of CSR endowed with a unique importance and, especially, with the potential to provide tremendous value added to business reputation. However, it seems, several obstacles hinder this purpose, the challenge is, despite all the difficulties we may find, identify the right way to overcome them.